“Remodeling the intestinal immune microenvironment”: immune regulation and tissue regeneration by mesenchymal stem/stromal cells in the repair microenvironment of inflammatory bowel disease - Li, Hongkun; Zhang, Yuyue; Du, Simin; Shen, Jinghan; Liu, Xingyan; Jing, Jie (Frontiers in Immunology, 2025)
The global prevalence of inflammatory bowel disease (IBD) has significantly increased in recent decades. IBD is a long-term, recurring, gastrointestinal inflammatory condition that mainly comprises two primary clinical types: ulcerative colitis and Crohn’s disease. The current treatment paradigm for IBD primarily focuses on symptom management. However, this approach does not support mucosal epithelial repair, maintenance of barrier homeostasis, or regulation of biological functions in the gut. Conventional therapies rely on the frequent use of high-dose medications, including antibiotics, nonsteroidal anti-inflammatory drugs, biological agents, and immunomodulators. Recently, mesenchymal stem/stromal cells (MSCs) have gained interest in tissue regeneration owing to their unique ability to differentiate and secrete regulatory factors, including extracellular vesicles (EVs), which play crucial roles in abnormal organization. Various routes of administration have been explored in preclinical and clinical studies to deliver MSCs from diverse tissue sources. The routes include intraperitoneal, intravenous, and local (intracolonic or rectal) delivery. The MSCs employed were obtained from various tissues, including bone marrow, umbilical cord, and adipose tissue. This article reviews the research framework for the application of MSCs and EVs secretion in the treatment of IBD, emphasizing key immunological effects, such as immune microenvironment regulation, intestinal barrier stabilization, and therapeutic approaches targeting intestinal barrier disorders. The discussion primarily focuses on the advantages of MSCs over other biologics, impairment of gut mucosal tissue-resident mesenchymal stem cells in IBD development, immune targets (at the cellular and molecular levels) within the framework of IBD, and the reparative effects of MSCs in the microenvironment of IBD. We aimed to present an overview of the current trends in MSC research and therapy, as well as to identify the challenges and future directions that must be addressed to advance research on MSC-mediated therapeutic strategies for IBD.